Penerapan Pembelajaran Inkuiri Terbimbing dengan Pendekatan Concrete-Representational-Abstract dalam Meningkatkan Kemampuan Pemecahan Masalah Siswa SMP - Afri, Lisa Dwi (Math Educa Journal, 2017)
This research is motivated by the importance and still not optimal problem solving ability of student mathematical problem. This study examines the improvement of students 'mathematical problem-solving abilities that acquire Guided Inquiry learning with Concrete-Representational-Abstract approach (ITCRA) and students who have received conventional learning, in terms of overall and math skills categories KAM (high, middle, low). This research is a quasi experiment with non-equivalent control group design. The population is grade VIII SMPN 1 Padang Panjang Lesson Year 2014/2015, and the samples are two classes from seven existing classes. Instruments used in the form of tests, observation sheets, and interview guidelines. The data obtained were analyzed using the difference test, ie t-test and mann-whitney. The results showed that: 1) The achievement and improvement of mathematical problem solving ability of students who received ITCRA learning overall better than those who received conventional learning, 2) the increased mathematical problem solving ability of moderate KAM and low KAM better than those with conventional learning, whereas in high KAM, students who received ITCRA learning was no better than that of conventional learning, and 3) there was a difference in the improvement of students' mathematical problem solving abilities of high KAM categories with KAM moderate and low category students who received ITCRA learning. However, there were no significant differences between moderate and low KAM category studentsKeywords: Guided Inquiry, concrete-representational-abstact, problem solving